Controle das propriedades estruturais, ópticas e eletrocatalíticas de nanocompósitos de óxidos semicondutores obtidos por aquecimento com micro-ondas - Romeiro, Fernanda da Costa (2018)
Samples of pure ZnO and TiO2 and nanocomposites of rGO-ZnO, rGO-TiO2 and rGO-TiO2-ZnO were successfully prepared by microwave assisted hydrothermal method. In microwave hydrothermal conditions, the reduction of graphene oxide (GO) to reduced graphene oxide (rGO). FE-SEM images showed that the nanoparticles become well dispersed on the rGO sheets. The Raman spectroscopy showed the active vibrational modes of the ZnO, GO and TiO2 anatase wurtzite structure, confirming the obtaining of the nanocomposites of rGO-ZnO, rGO-TiO2 and rGO-TiO2-ZnO. In relation to the band gap value of the pure ZnO and TiO2, the band gap values of the nanocomposites decreased. The nanocomposites of rGO-TiO2 and 16rGO-TiO2-ZnO containing greater amount of rGO showed two band gap values, which may be related to the formation of chemical bonds between Ti-O-C. The introduction of GO promoted a decrease in the intensity of photoluminescence emission compared to pure oxides, suggesting that the transfer of electrons from the oxides to the rGO sheets decreases the electron recombination in the nanocomposites. The resulting nanocomposites exhibited high current density and stability which were resulted from the electronic interaction between the ZnO and TiO2 nanoparticles with the rGO sheets. The presence of rGO in the nanocomposites increased the charge separation of the electron hole-pair, resulting in a greater electrocatalytic effect in the water oxidation. In addition to these results, small CoOx@NC nanoparticles was successfully synthesized by thermal treatment of Co(TCNQ)2 at different calcination temperatures. The results of XRD showed the possible formation of a mixture of phases related to the cubic CoO structure and to the spinel-type Co3O4 phase. The microscopy images revealed that cobalt nanoparticles were homogeneously distributed in the carbon rod structures. The CoOx@NC nanocomposite obtained at 400°C exhibited the higher activity for oxygen evolution reaction and hydrogen evolution reaction in alkaline media, with high stability and current density attributed to the synergistic effect of the carbon matrix and cobalt oxide.